Critical Thinking and Sustainability Awareness of Accounting Students in Higher Education - Sulastri; Diana Tien Irafahmi; Darpiyah (HM Publisher, 2023)
Sustainability awareness is students' continuous awareness to protect and respect the environment and life surroundings. Awareness of environmental sustainability is one of the prerequisites for environmental attitudes and behavioral changes in caring for the natural environment in the face of climate change and global warming. Higher education holds the responsibility to form students with environmental awareness and change the attitudes of future generations towards the importance of preserving the natural environment. Sustainability awareness is influenced by critical thinking. Critical thinking is the process of making judgments based on the processes of analysis, interpretation, evaluation, inference, explanation and reflection. This research uses simple regression analysis techniques. The research results prove that critical thinking influence on sustainability awareness.